Parent's Participation in Improving the Quality of Education in Elementary Schools - Aulia, Mifta; Amra, Abhanda (Universitas Islam negeri Mahmud Yunus Batusangkar, 2021)
ParentsÔÇÖ low participation in improving the quality of education is an interesting topic of study. This research aims to obtain data on parentsÔÇÖ participation in improving the quality of infrastructure and learning process in elementary schools. This research used a qualitative descriptive approach. Sources of data were the principal, teachers, and parents. Data collection techniques were observation, interviews, and documentation. Based on the research findings, it can be discussed that parents already participated in improving educational infrastructure but not maximized. They donate funds and energy for school construction. While, in learning process, parents contribute to guide, to motivate, to supervise the children, and to facilitate all their needs in learning. Problems faced by parents in improving the quality of learning are lack of time in supervising the children to learn due to busy work and also the low level of parentsÔÇÖ education and income (education and economic factors).